Extracorporeal shockwave therapy for tendinopathies: a comprehensive literature review - K., Prasanth; B., Riyas Basheer K.; P., Madhuripu; A., Femina Hameed V. (International Journal of Research in Medical Sciences, 2025)
Tendinopathies, including Achilles, patellar, lateral epicondylitis, and plantar fasciitis, are chronic musculoskeletal disorders with limited responsiveness to conventional therapies. Extracorporeal shockwave therapy (ESWT), a non-invasive intervention, has emerged as a promising modality targeting both symptomatic relief and structural regeneration. To synthesize high-level evidence on the efficacy and mechanisms of ESWT in managing tendinopathies, emphasizing randomized controlled trials (RCTs), treatment protocols, patient outcomes, and methodological quality. Following preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines, a comprehensive search of four databases was conducted for English-language RCTs published between 2000 to 2024. Inclusion criteria focused on ESWT interventions for tendinopathies with reported clinical outcomes. Quality was assessed using the PEDro scale and Cochrane Risk of Bias 2.0 tool. Four RCTs involving 432 participants were included, addressing plantar fasciitis, Achilles tendinopathy, lateral epicondylitis, and patellar tendinopathy. ESWT demonstrated significant reductions in pain (VAS), improved functional scores (VISA-A, RM, AOFAS), and structural recovery. Focused ESWT showed deeper penetration and neovascularization benefits, while radial ESWT was more effective for superficial lesions. Variability in energy flux densities and session protocols influenced therapeutic response. PEDro scores ranged from 6 to 9, with low-to-moderate risk of bias. ESWT offers effective, non-invasive treatment for various tendinopathies, especially when conventional options fall short. Future research should emphasize protocol standardization, long-term outcome evaluation, and comparative efficacy with other regenerative modalities.